Barriers to and enablers of type 2 diabetes screening among women with prior gestational diabetes: A qualitative study applying the Theoretical Domains Framework - Lake, Amelia J.; Williams, Amelia; Neven, Adriana C. H.; Boyle, Jacqueline A.; Dunbar, James A.; Hendrieckx, Christel; Morrison, Melinda; O’Reilly, Sharleen L.; Teede, Helena; Speight, Jane (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction Women with previous gestational diabetes mellitus (GDM) are at increased risk of type 2 diabetes (T2D). Guidelines recommend postnatal diabetes screening (oral glucose tolerance test or HbA1c) typically 6-12 weeks after birth, with screening maintained at regular intervals thereafter. Despite this, around half of women are not screened, representing a critical missed opportunity for early identification of prediabetes or type 2 diabetes. While policy and practice-level recommendations are comprehensive, those at the personal-level primarily focus on increasing screening knowledge and risk perception, potentially missing other influential behavioral determinants. We aimed to identify modifiable, personal-level factors impacting postpartum type 2 diabetes screening among Australian women with prior gestational diabetes and recommend intervention functions and behavior change techniques to underpin intervention content. Research design and methods Semi-structured interviews with participants recruited via Australia’s National Gestational Diabetes Register, using a guide based on the Theoretical Domains Framework (TDF). Using an inductive-deductive approach, we coded data to TDF domains. We used established criteria to identify ‘important’ domains which we then mapped to the Capability, Opportunity, Motivation–Behavior (COM-B) model. Results Nineteen women participated: 34 ± 4 years, 19 ± 4 months postpartum, 63% Australian-born, 90% metropolitan, 58% screened for T2D according to guidelines. Eight TDF domains were identified: ‘knowledge’, ‘memory, attention, and decision-making processes’, ‘environmental context and resources’, ‘social influences’, ‘emotion’, ‘beliefs about consequences’, ‘social role and identity’, and ‘beliefs about capabilities’. Study strengths include a methodologically rigorous design; limitations include low recruitment and homogenous sample. Conclusions This study identified numerous modifiable barriers and enablers to postpartum T2D screening for women with prior GDM. By mapping to the COM-B, we identified intervention functions and behavior change techniques to underpin intervention content. These findings provide a valuable evidence base for developing messaging and interventions that target the behavioral determinants most likely to optimize T2D screening uptake among women with prior GDM.